No Parking Here to Corner: London Reshaped by the Automobile, 1911-61 - Bloomfield, Gerald (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1989)
The motor vehicle has been a powerful force reshaping cities in the 20th century. This study, with a focus on London, Ont., examines the role of the automobile in urban areas. Motorization, highway development, and the growth of the automotive business sector are considered in three phases of growth. Until the late 1930s the automobile could be accommodated within the existing urban structure with only comparatively minor changes. The increase of traffic congestion after this period, however, was a compelling force in the decentralization of activities to a new suburban zone. Wider ownership of automobiles in the 1950s resulted in greater consumer mobility, which in turn was a major contributor to the development of a new physical layout for London.